Characteristics of a Danish population of adults with acquired deafblindness receiving rehabilitation services. (September 2013) - Dammeyer, Jesper
The aim of this study is to report on the characteristics of a population of 916 individuals with acquired deafblindness receiving national Danish counselling and rehabilitation services. Age, gender, prevalence, social status, and communication mode are some of the data included in this study. Results show that 70% of the population was older than 79 years, 15% was between 65 and 79 years, and 15% of the population was younger than 65 years. Oral speech was used by 86%, sign language by 10%, and tactile sign language by 4%. Among individuals younger than 65 years, less than 50% was employed or in education. Results are discussed with respect to the organization of the Danish counselling and rehabilitation service system.